A Comprehensive Study of Bipolar Vague Soft Expert P-Open Sets in Bipolar Vague Soft Expert Topological Spaces with Applications to Cancer Diagnosis (European Journal of Pure and Applied Mathematics, 2025)
We rigorously examine the concept of bipolar vague soft expert sets (BPVSESs) and their defining characteristics. Fundamental operations such as complement, union, and intersection are firmly established as foundational elements of the framework. Additionally, the notion of bipolar vague soft expert topology (BPVSET) is introduced, along with eight innovative definitions. Among these, the definition of the bipolar vague soft expert pre-open set, often abbreviated as the p-open set, is particularly significant for constructing diverse structures. This study also provides a strong and healthy articulation of the concepts of interior and closure, offering a detailed exploration of their interactions. Furthermore, it develops foundational topological concepts in bipolar vague soft expert topology by introducing and analyzing bases, sub-bases, and local bases. The notions of first and second countability in the bipolar vague soft expert topology context are formally defined, while separability is explored via countable dense sets. These results enhance the theoretical framework of bipolar vague soft expert topological space, supporting soft topological modeling under uncertainty and parameterization. A comprehensive investigation into these foundational concepts culminates in a series of compelling results concerning the basis of bipolar vague soft expert topological spaces. Finally, it introduces a decision-making framework based on bi-polar vague soft expert sets to support cancer diagnosis.
Keywords: Vague set, bipolar vague set, bipolar vague soft set, bipolar vague soft topology, bipolar vague soft p-open set